STUDI KASUS PERILAKU NEGATIF ANAK USIA 6 TAHUN DI DESA TANJUNG LAUT - Marintan, Tiara; Dwi Suryani, Yuni (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the process of imitating negative behavior and itsimpact on 6-year-old children in Tanjung Laut Village. The study used a qualitativemethod with a case study approach. The subject was a child identified as AF. Datawere collected through observation, interviews, and documentation, then analyzedthrough data reduction, data presentation, and conclusion drawing. The resultsshowed that the negative behaviors that emerged included physical aggression,verbal aggression, and disobedience to rules. These behaviors were formedthrough imitation, influenced by family parenting styles and exposure to socialmedia. The impacts are seen in children's social-emotional development, such aslow empathy, difficulty controlling emotions, and disrupted peer relationships.